The use of nicardipine prolonged release implants (NPRI) in microsurgical clipping after aneurysmal subarachnoid haemorrhage: comparison with endovascular treatment - Schneider, Ulf Christoph; Dreher, Stefanie; Hoffmann, Karl-Titus; Schmiedek, Peter; Kasuya, Hidetoshi; Vajkoczy, Peter (Acta neurochirurgica, 2011)
Nicardipine prolonged release implants (NPRI) have been shown to decrease the incidence of cerebral vasospasm and infarcts significantly in patients after aneurysmal subarachnoid haemorrhage (SAH) following microsurgical clipping. Yet, the comparison with results after endovascular coiling is lacking. This study was conducted to determine the differences in the incidence of cerebral vasospasm and infarctions between those two treatment modalities